Effect of Horizontal-Agency-Costs and Managerial Ownership on Monitoring Mechanisms - Arowolo, Rachael Oluyemisi; Che-Ahmad, Ayoib (International Journal of Economics and Financial Issues, 2016)
There is a level of information asymmetry between the agents (management and the board of directors) and the principal (shareholders) in every company. The purpose of this study is to examine the scope of monitoring mechanisms in non-financial listed companies of Nigeria. This paper also investigates the impact of managerial ownership and horizontal-agency-costs on the mechanisms. Panel-corrected standard errors in Stata 12 application was used to test the hypotheses. The result suggests that the horizontal-agency-cost positively relates to monitoring mechanisms. It also provides evidence that managerial ownership has a significant negative impact on monitoring mechanisms. These findings suggest policy implications to the board of directors, the internal and external auditors on their monitoring roles. Likewise, the findings are beneficial to the government and regulatory agencies for possible further review of the guidelines on corporate governance. This paper contributes to knowledge in Sub-Saharan Africa by combining directorship, internal and external auditing as dimensions of monitoring mechanisms in a single study. Also, it examines horizontal-agency-cost, which is an emerging topic in Nigeria. Keywords: Monitoring mechanisms, Horizontal-agency-costs, Managerial ownership JEL Classifications: M40; M41; M42